When Abangan Embraces Sufism: Religious Phenomenology to Counter Radicalism in Contemporary Java - Amanah Nurish (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
Abangan is one of the socio-religious groups regarded as a marginal community among the trichotomy of santri and priayi. It has been known that abangan were not religious Muslim, and they are poor farmers as well as workers, backward and less educated people. Meanwhile, santri are more religious and priayi among Javanese society are middle-class people practising syncretic Islam. The thesis on “The Religion of Java,” by Clifford Geertz, was more than a half-century indicated religious and social classification in Javanese society. In the midst of political polarization of Indonesian reformation, transnational Islamic groups began to establish their movement widely. Transnational Islamic groups that promote radicalism and violent extremism clearly avoid local wisdom and mysticism. As a result, abangan has experienced dramatic religious and social change. This study aims to see how to face radicalism after reformation in the social and religious transformation of abangan in Java. Previous studies have shown that the phenomenon of radicalism affects religious intolerance addressed to minority groups like abangan. This research paper aims to examine how abangan reacts to radicalism and engages with Sufism and their devotion to tarekat. Abangan recently appears to convert and join the tarekat movement as an alternative discourse to encounter modernism and religious radicalism.